Web-GIS models: accomplishing modularity with aspects - Urbieta, Mario Matías (2013)
Spatial concerns of Web geographical information systems (Web-GIS) are inherently crosscutting and volatile: crosscutting because they affect multiple functionalities of Web-GIS systems, and volatile because their status may change often. If these concerns are not modularized properly, the quality of Web-GIS services, particularly with regard to adaptation and evolution, can be severely compromised. This paper uses aspect-orientation to model crosscutting and volatile spatial concerns. By modeling both types of concerns, crosscutting and volatile, as candidate aspects, one can use dynamic weaving to add or remove them from a system at runtime. The aspect-oriented approach proposed starts with the identification and specification of crosscutting concerns and follows by composing these using modeling aspects using a transformation approach, an aspect-oriented modeling technique. The conflicts that can emerge due to the composition order are also taken into consideration. Finally, this paper proposes a set of reusable GIS crosscutting concerns, documenting them in a concern catalogue.